Spatial Analysis of Air Quality in the area of Imam Turki bin Abdullah Royal Reserve In the Kingdom of Saudi Arabia - Al-Dughairi, Ahmed Abdullah (Journal of natural sciences, life and applied sciences, 2023)
The Imam Turki bin Abdullah Royal Reserve occupies parts of Northern and Central Saudi Arabia, and includes parts of Al-Qassim, Hail, the Eastern region and the Northern borders. This research is derived in solidarity with the vision of the kingdom of Saudi Arabia, which strives tirelessly in the development and management of its natural reserves, which have suffered and still are from environmental stress that has lasted for long periods of time. The study aims to shed light on the air quality in the reserve during the peak period, which starts around Eleven o’clock During 1444 and lasts for hours, from which the developer can observe the sites where he is considering to conduct more detailed in-depth studies of air quality conditions, especially those that affect the growth of natural vegetation in the Reserve. In order to provide an accurate analysis of the spatial distribution of air quality in the Reserve, we have relied on Spatial Analysis Techniques Interpolation IDW, and thermal values were analyzed from Terraclimate data with spatial clarity (4×4 km) as obtained from the Climate Engine platform, the analytical results have shown ideal values in the quality of its air, in terms of distance from industrial influences, or sources of pollution, the study also showed the presence of a relative effect of aerosols in the East and north sites of the reserve due to emissions from some surrounding factories and rock grinding projects in the surrounding cities and abandonment, possibly the product of car exhaust combustion in the roads connecting the territory of the Reserve is exposed to the effects of rushing aerosols during the surface or upper layers of the atmosphere, but the values support it, as being in moderate values that do not adversely affect the environment of the reserve.